1994
DOI: 10.3406/polix.1994.1843
|View full text |Cite
|
Sign up to set email alerts
|

Procès, affaire, cause. Voltaire et l'innovation critique

Abstract: The Trial, the Case, the Cause. Voltaire and the critical innovation. Elisabeth Claverie [76-851 In the 1760's, Voltaire took on the impassioned defense of a number of people accused of crime by judges of Parlement (Calas, Sirven, Chevalier de la Barre). Undertaking this defense meant accusing and, as a consequence, transforming the judiciary arena, in which procedures were secret, into a public arena. The innovation introduced by Voltaire during the Calas case was that, in order to defend him… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
16

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 0 publications
0
8
0
16
Order By: Relevance
“…Mais la temporalité peut encore être décon-nectée du support biographique des personnes et de la moyenne durée des affaires publiques. Dans le court terme, l'enquête peut suivre la temporalité de moments d'épreuve qui provoquent des mobilisations soudaines -qu'il s'agisse d'événements comme celui de la profanation du cimetière de Carpentras (Barthélémy, 1991) ou de disputes, comme les affaires Calas et du Chevalier de la Barre (Claverie, 1994(Claverie, et 1998. Elle peut encore prendre la forme des controverses que les étudiants de l'École des Mines et de Sciences Po étudient aujourd'hui, emboîtant le pas à l'entreprise de Latour depuis son étude sur la « pasteurisation de la France » (Latour, 1984) -avec, dans l'étude des dispositifs d'action publique, un recroisement entre les conceptions de sociologie des organisations, des cités de justification, et des sciences et des techniques (Lolive, 1999).…”
Section: Comment Se Mobilise-t-on ?unclassified
“…Mais la temporalité peut encore être décon-nectée du support biographique des personnes et de la moyenne durée des affaires publiques. Dans le court terme, l'enquête peut suivre la temporalité de moments d'épreuve qui provoquent des mobilisations soudaines -qu'il s'agisse d'événements comme celui de la profanation du cimetière de Carpentras (Barthélémy, 1991) ou de disputes, comme les affaires Calas et du Chevalier de la Barre (Claverie, 1994(Claverie, et 1998. Elle peut encore prendre la forme des controverses que les étudiants de l'École des Mines et de Sciences Po étudient aujourd'hui, emboîtant le pas à l'entreprise de Latour depuis son étude sur la « pasteurisation de la France » (Latour, 1984) -avec, dans l'étude des dispositifs d'action publique, un recroisement entre les conceptions de sociologie des organisations, des cités de justification, et des sciences et des techniques (Lolive, 1999).…”
Section: Comment Se Mobilise-t-on ?unclassified
“…It is tempting to draw a parallel with the Calas affair, a case of apostasy that arose in eighteenth-century France (Claverie 1994). Voltaire, the mastermind behind the affair, showed that he had no personal interest whatsoever in the case and that his only concern was to promote a ÒcauseÓ, or a Ògood cause.Ó 14 He used this ÒcauseÓ to mobilize the general interest over and above particular interests for the benefit of Òthe public goodÓ.…”
Section: The Political Motivementioning
confidence: 99%
“…Their dissemination in the media and the fact that they implicated actors at different levels such as governments from different jurisdictions, multilateral bodies, international courts and the Supreme Court of Justice, among others, have contributed to making these conflicts destabilizing cases for state action. They constitute scandals that exemplify a state of things and that, from the perspective of the social analyst, allow for the understanding of certain aspects of the problem under analysis (CLAVÉRIE, 1994;DE BLIC and LEMIEUX, 2005;BOLTANSKI ET. AL., 2007).…”
Section: Introductionmentioning
confidence: 99%